Implementation of the SKUA Program to Strengthen Students’ Ubudiyah Values in Islamic Education Learning - Aisyah Yulfah Nur Alfiyani; Muhammad Rohmad Abdan; Fithri Hidayati (Program Studi Pendidikan Guru Madrasah Ibtidaiyah INSURI Ponorogo, 2026)
This study aims to analyze the implementation of the SKUA (Standard Competency of Ubudiyah and Akhlakul Karimah) Program in strengthening students’ ubudiyah values in Islamic Religious Education (PAI) learning at MTs Ma’arif Cipta Insan Mulya. The research employed a qualitative case study approach conducted at the madrasah during the 2024/2025 academic year. Data were collected through observation, in-depth interviews, and documentation, involving 1 madrasah principal, 3 PAI teachers, 2 SKUA instructors, and 12 students purposively selected based on their involvement in the program. Data analysis used the interactive model of Miles, Huberman, and Saldaña, including data condensation, data display, and conclusion drawing, while validity was ensured through source and technique triangulation. The findings reveal that the SKUA Program is implemented systematically through planning, implementation, evaluation, and continuous development stages. The program integrates worship habituation activities such as congregational Dhuha and Dhuhur prayers, Qur’an recitation, memorization of daily prayers, ablution and prayer practices, and the cultivation of Islamic manners. The program has significantly improved students’ worship discipline, spiritual awareness, and consistency in practicing ubudiyah both at school and at home. However, several obstacles were identified, including limited guidance time, differences in students’ Qur’an reading abilities, and limited parental supervision. The novelty of this study lies in presenting SKUA as a competency-based worship education model integrated with structured evaluation of students’ worship practices. This study implies that competency-based religious habituation programs can strengthen the effectiveness of Islamic Religious Education in developing students’ religious character and devotional values.